2001
DOI: 10.1103/physrevlett.86.3160
|View full text |Cite
|
Sign up to set email alerts
|

C13NMR Chemical Shift of Single-Wall Carbon Nanotubes

Abstract: We compute the magnetic shielding tensor within the London approximation and estimate the Knight shift of single-wall carbon nanotubes. Our results indicate that high resolution 13 C NMR should be able to separate the metallic and insulator character of the nanotubes since a 11 ppm splitting is predicted from the respective resonances. As a model for disorder, bending, and defects in these structures, we investigate the magnetic response of nanotubes with finite size. We get a small line broadening coming from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
77
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(91 citation statements)
references
References 21 publications
12
77
2
Order By: Relevance
“…isotropic) and dipolar, and exclude the third one, orbital HF (OHF) [32]. It should be noted that the consequences of OHF in nuclear magnetic resonance of CNTs [33,34] and graphene [35] have been analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…isotropic) and dipolar, and exclude the third one, orbital HF (OHF) [32]. It should be noted that the consequences of OHF in nuclear magnetic resonance of CNTs [33,34] and graphene [35] have been analyzed.…”
Section: Introductionmentioning
confidence: 99%
“…Among different nuclei, 13 C NMR is a sensitive probe to the local electronic environment of CNTs. 16,24,25 However, a wealth of literature 26−29 has so far focused only on the direct measurement of CNTs using 13 C isotope enrichment technique. To the best of our knowledge, there is no systematic 13 C NMR investigation that involves the study of 13 C-enriched guest molecules confined inside CNTs.…”
Section: Introductionmentioning
confidence: 99%
“…[15] Unfortunately, due to the magnetic properties of 3 it is actually impossible to further characterize this material by using solid state NMR spectroscopy. [16] From the transmission electron microscopy (TEM) analyses of MNP-PIDA 3, it was confirmed that well separated nanoparticles with a size distribution ranging from 8 to 20 nm were homogeneously dispersed over the entire area (Figure 2, left), such polydispersity is expected from of the protocol chosen for the synthesis of magnetic nanoparticles. Note that the particles showed slight aggregation after 8 times recycling (Figure 2, right), presumably because the moieties on the MNP surfaces are less effective in preventing the aggregation of the MNP (upon solvent evaporation).…”
mentioning
confidence: 63%